Current perspectives on the early identification and management of delirium after acute stroke reperfusion therapy - Hao, Ya-Nan; Feng, Xiao-Yang; Wu, Fei; Yang, Xiao-Dan; Zhang, Xiao-Ling (Frontiers in Neurology, 2025)
Delirium is a common and severe complication following acute cerebral ischemic stroke reperfusion, affecting cognitive and motor recovery and associated with poor long-term outcomes, prolonged hospitalization, increased readmission, and higher mortality. Identifying risk factors, understanding the pathogenesis (especially reperfusion injury), and implementing early intervention are crucial. However, the complex etiology and limited efficacy of drug treatments make early detection and management challenging. Recent studies have identified factors such as age, NIHSS score, pre-stroke cognition, and post-reperfusion inflammation, along with biomarkers, as predictors of delirium. Family involvement and environmental optimization may also reduce risk. This review summarizes current evidence on risk factors, pathogenesis, biomarkers, and interventions to improve early identification, reduce disability, and improve prognosis.